Environmental impact of digital financial inclusion and green growth: Insights from global panel data analysis - Muhammad Tariq Majeed; Maria Mazhar; Zubia Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This paper analyzes the environmental effects of digital financial inclusion (DFI) along with green growth using panel data from 102 economies over the period 1990-2022. The analysis used mobile cellular subscriptions (MCSs), bank branches (BB), and automated teller machines (ATMs) as proxy variables of DFI. The empirical results are estimated employing Pooled Ordinary Least Square (POLS) and Method of Moments Quantile Regression (MMQR) estimation approaches. The findings suggest that an increase in DFI reduces environmental quality. Intriguingly, a comparative assessment of DFI measures indicates that while an increase in MCSs is associated with an enhancement of environmental quality, the proliferation of BB and ATMs tends to diminish it. The analysis shows that green economic growth leads to lower emissions. The environmentally improving effect of green growth remains robust across all quantiles. The analysis also validates the Pollution Halo Hypothesis, shedding light on the point where expanding economies begin to curtail environmental degradation. Altogether, this study enhances the literature by conducting a comprehensive analysis of the interplay between DFI, green growth, and environmental quality, offering valuable insights for policy formulation in the contemporary digitally driven and environmentally aware global landscape
Keywords: 330; CO2 emissions; financial inclusion; ATMs; mobile cellular subscriptions; bank branches; urbanization; energy use; digital financial inclusion index